Transnational policy networks and international nongovernmental organizations as human security agents - Τζιφάκης, Νικόλαος (The Greek Review of Social Research, 2014)
Public and private actors systematically consult, cooperate and coordinate their efforts to promote human security within transnational policy networks. The article analyses the operation of these networks, focusing on the participation of International NGOs (INGOs). It argues that the contribution of INGOs (and by extension other private actors) to the resolution of international problems is not constant and uniform across time and space. It is instead differentiated from one case to another and determined by the functions that these actors are called to perform, as well as by the structures of the policy networks in which they participate.